Evaluation of cell growth performance of microalgae Chlorella minutissima using an internal light integrated photobioreactor. Issue 5 (October 2020) - Amaral, M.S.; Loures, C.C.A; Naves, F.L.; Baeta, B.E.L.; Silva, M.B.; Prata, A.M.R.
Graphical abstract: Highlights: The ILI-PBR combines the advantages of tubular and bubble column photobioreactor in a single integrated configuration. μ max and PX in ILI-PBR were at least 42.85 and 58.06 % higher than ILBC-PBR, respectively. ILI-PBR was 36 % more efficient in terms of electricity consumption than the internal bubble column photobioreactor. Abstract: Microalgae have received special attention due to the biotechnological potential of their biomass, which can be used to produce biofuels, food formulations and pharmaceutical products. In order to improve biomass productivity, the present work proposes an internal light integrated photobioreactor (ILI-PBR), which integrates two configurations of photobioreactors (PBRs) already consecrated and widely used (tubular and bubble column) in a single system, combining the benefits of each configuration in a single PBR. To evaluate the applicability of ILI-PBR, a comparative test was conducted with the internal light bubble column photobioreactor (ILBC-PBR); both PBRs were illuminated with blue light-emitting diodes (LED).The PBR's performance was evaluated in terms of specific growth rate (μ max ) and cell productivity ( PX ) of the microalgae Chlorella minutissima . The μ max and PX in ILI-PBR were at least 42.85 and 58.06 % higher than ILBC-PBR, respectively. ILI-PBR was 36 % more efficient in terms of electricity consumption than ILBC-PBR.